Nature-based tourism, conservation and institutional governance: a case study from the Russian Arctic. Issue 1 (2nd January 2016) - Pashkevich, Albina; Stjernström, Olof; Lundmark, Linda
Abstract: This paper analyses current institutional arrangements connected to the protection of natural resources in developing nature-based tourism in the territories of the north-western part of the Russian Arctic. Examples from two regions, the Arkhangelsk Oblast and the Nenets Autonomous Okrug, illustrate how the different methods of nature conservation – national parks and nature reserves – are promoting or constraining the development of nature-based tourism activities. The study is based on 14 semi-structured interviews with representatives from state organisations as well as representatives from non-governmental organisations, and reviews of planning and policy documents. This paper discusses the factors shaping present institutional arrangements connected to environmental protection and the capability to establish planning schemes. The agencies responsible for nature-based tourism development often suffer from rudimentary tourism planning, inadequate tourism infrastructure and a lack of service management skills. In addition, there is evidence that mistrust and a lack of collaboration among governmental agencies and private stakeholders also limit development opportunities. Despite the difficulties experienced by authorities responsible for the measures of conservation and nature protection in the remote Arctic territories (Nenetsky State Nature Reserve), pockets of success are identifiable (e.g. Kenozersky National Park). The reality of the nature conservation efforts and the ability to develop nature-based activities is heavily dependent on individual engagement and interpersonal collaboration, which makes the best practices non-transferable to other contexts. So far, the current system of institutional governance limits the possibilities to increase the economic impact of nature-based tourism in the Russian Arctic.